Chemical Properties of Cerium (III) Hexacyanoferrate (II/III) on Graphene Oxide Chemically Modified with a PAMAM Dendrimer and Application as a Sensor for l-Dopamine Detection - Bonfim, Kely Silveira [UNESP]; Peixoto, Murilo dos Santos [UNESP]; do Carmo, Devaney Ribeiro [UNESP] (Wiley, 2025)
A novel functional platform comprising graphene oxide (GO) and a PAMAM dendrimer (GO-PAMAM) is presented herein, subsequently modified with Ce(III) ions and potassium hexacyanoferrate (III) to form a complex incorporating hexacyanoferrate (II/III) redox species. The resulting hybrid material was characterized by different spectroscopic techniques such as X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and cyclic voltammetry studies. Electrochemical assessments, specifically cyclic voltammetry, demonstrated the suitability of the modified electrode for the electrocatalytic detection of l-dopamine. A linear response was observed from 2.0 × 10⁻⁶ to 4.0 × 10⁻⁵ mol L⁻¹. The limit of detection was 4.09 × 10⁻⁷ mol L⁻¹ with a standard deviation of ±3% (n = 3), while amperometric sensitivity was determined as 195.28 mA/mol L⁻¹.
Keywords: Cerium hexacyanoferrate; Dopamine; Graphene oxide; PAMAM dendrimer; Voltammetry